Feasibility of three‐dimensional MRI of proximal femur microarchitecture at 3 tesla using 26 receive elements without and with parallel imaging. Issue 1 (29th October 2013) - Chang, Gregory; Deniz, Cem M.; Honig, Stephen; Rajapakse, Chamith S.; Egol, Kenneth; Regatte, Ravinder R.; Brown, Ryan
<x xml:space="preserve">Abstract</x> Purpose High‐resolution imaging of deeper anatomy such as the hip is challenging due to low signal‐to‐noise ratio (SNR), necessitating long scan times. Multi‐element coils can increase SNR and reduce scan time through parallel imaging (PI). We assessed the feasibility of using a 26‐element receive coil setup to perform 3 Tesla (T) MRI of proximal femur microarchitecture without and with PI. Materials and Methods This study had institutional review board approval. We scanned 13 subjects on a 3T scanner using 26 receive‐elements and a three‐dimensional fast low‐angle shot (FLASH) sequence without and with PI (acceleration factors [AF] 2, 3, 4). We assessed SNR, depiction of individual trabeculae, PI performance (1/g‐factor), and image quality with PI (1 = nonvisualization to 5 = excellent). Results SNR maps demonstrate higher SNR for the 26‐element setup compared with a 12‐element setup for hip MRI. Without PI, individual proximal femur trabeculae were well‐depicted, including microarchitectural deterioration in osteoporotic subjects. With PI, 1/g values for the 26‐element/12‐element receive‐setup were 0.71/0.45, 0.56/0.25, and 0.44/0.08 at AF2, AF3, and AF4, respectively. Image quality was: AF1, excellent (4.8 ± 0.4); AF2, good (4.2 ± 1.0); AF3, average (3.3 ± 1.0); AF4, nonvisualization (1.4 ± 0.9). Conclusion A 26‐element receive‐setup permits 3T MRI of proximal femur microarchitecture with good image quality up to PI AF2. J. Magn. Reson. Imaging 2014;40:229–238. © 2013 Wiley Periodicals, Inc.